2017
DOI: 10.3892/or.2017.6020
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA-MIAT regulates cell biological behaviors in gastric cancer through a mechanism involving the miR-29a-3p/HDAC4 axis

Abstract: Gastric cancer (GC) is one of the most common malignant diseases worldwide. Although significant progress has been made in the early detection and treatment of GC over the past decades, the prognosis is still not satisfactory and the underlying mechanisms of carcinogenesis remain unknown. Long non-coding RNA MIAT has been established as a key player in the regulation of various biological and pathological processes including chronic lymphocytic leukemias, acute myocardial infarction and neuroendocrine prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…It is well known that lncRNAs act as ceRNA to regulate functional gene expression via sponging miRNAs . In the previous studies, MIAT was reported to function as ceRNA in ccRCC, colorectal cancer, breast cancer, gastric cancer and non‐small‐cell lung cancer . Therefore, we speculated that MIAT might function as an oncogene through a ceRNA manner.…”
Section: Discussionmentioning
confidence: 90%
“…It is well known that lncRNAs act as ceRNA to regulate functional gene expression via sponging miRNAs . In the previous studies, MIAT was reported to function as ceRNA in ccRCC, colorectal cancer, breast cancer, gastric cancer and non‐small‐cell lung cancer . Therefore, we speculated that MIAT might function as an oncogene through a ceRNA manner.…”
Section: Discussionmentioning
confidence: 90%
“…The human HDAC4 gene, located on chromosome 2q37.3, has been found to be involved in initiation and development of various cancers, and functions as an oncogene in many cancers [32][33][34][35][36]. A previous study confirmed HDAC4 as a target of miR-29b-3p in MM cells [25].…”
Section: Discussionmentioning
confidence: 94%
“…22,23 HDAC4, a member of the HDAC family, is overexpressed in GC, and plays multiple roles in the malignant characteristics of GC cells in vitro and in vivo. [33][34][35] Understanding the newly identified RGMB-AS1-miR-574-HDAC4 regulatory network can clarify the oncogenic activities of RGMB-AS1 in GC and may point to promising therapeutic regimens for patients with GC.…”
Section: Discussionmentioning
confidence: 99%